2022
DOI: 10.3390/agriculture12091320
|View full text |Cite
|
Sign up to set email alerts
|

Causal Linkage among Agricultural Insurance, Air Pollution, and Agricultural Green Total Factor Productivity in United States: Pairwise Granger Causality Approach

Abstract: Agricultural insurance and green agriculture are strongly related. Agricultural insurance not only motivates farmers to adopt environmentally friendly production technology and enhances the effectiveness of production, but it also accomplishes the goal of lowering the number of chemicals that are put into the environment. This article investigates the dynamic relationship between agricultural insurance, air pollution, and agricultural green total factor productivity. To complete the aim, the authors used the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 81 publications
1
27
0
Order By: Relevance
“…Li et al [ 30 ] analyzed the impact of agricultural insurance and air pollution on agricultural green TFP in China, and the results showed that agricultural insurance could improve agricultural green TFP. Similar studies include Ahmed et al [ 29 ]. Zou et al [ 31 ] studied the impact of agricultural insurance on China's agricultural output and pointed out that agricultural insurance promoted the growth of agricultural output by improving labor productivity and arable area.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Li et al [ 30 ] analyzed the impact of agricultural insurance and air pollution on agricultural green TFP in China, and the results showed that agricultural insurance could improve agricultural green TFP. Similar studies include Ahmed et al [ 29 ]. Zou et al [ 31 ] studied the impact of agricultural insurance on China's agricultural output and pointed out that agricultural insurance promoted the growth of agricultural output by improving labor productivity and arable area.…”
Section: Introductionsupporting
confidence: 68%
“…As a risk management tool, agricultural insurance effectively compensates for farmers' post-disaster losses and is conducive to the continuity and stability of agricultural production [ 28 ]. Many scholars have carried out research on agricultural insurance and its effects on household income, agricultural output and the rural economy [ [29] , [30] , [31] ]. Li et al [ 30 ] analyzed the impact of agricultural insurance and air pollution on agricultural green TFP in China, and the results showed that agricultural insurance could improve agricultural green TFP.…”
Section: Introductionmentioning
confidence: 99%
“…A higher value of green total factor productivity indicates a higher level of agricultural green development. Measurement models such as non-radial directional distance function models with global benchmarks and Luenberger productivity indices are used to assess the level of agricultural green development [25,38,40,[52][53][54][55][56]. On the other hand, agricultural carbon intensity measures the degree of greening in agriculture from the perspective of reducing emissions from agricultural non-point source pollution.…”
Section: Research On the Measurement Of Agricultural Green Developmen...mentioning
confidence: 99%
“…Wang et al (11) found that regulating the atmospheric environment can significantly inhibit the growth of industrial total factor productivity by selecting panel data from 37 industrial sectors in China from 2003 to 2016 as the research object. Using the panel vector auto-regressive method (PVAR) and panel data from 30 provinces in China between 2005 and 2018, Li et al (12) found that improving agricultural green total factor productivity by significantly reducing air pollution, in line with the work of Ahmed et al (13), who used the PMG method and panel data of 50 states of America from 2005 to 2019. Based on the data from 30 provinces on the China from 2004 to 2017, Liu et al ( 14) use the difference-in-differences (DID) method to find that the APPCAP policy has promoted the improvement of provincial energy efficiency.…”
Section: Introductionmentioning
confidence: 78%